Abstração inicial e valores CN em diferentes usos da terra no Cerrado com utilização de um simulador de chuva - Carvalho, Fábio (2018)
The study of response conditions to the process of precipitation and surface runoff is one of the challenges in hydrogeomorphological studies. Among existing studies, the CN method has become important due to its ease of application from the use of physical parameters, land use and occupation and precipitation data, estimating the runoff and potential storage of watersheds, providing hydrological information for decision-making by managers and researchers. The objective of this work is to obtain the initial abstraction volume (Ia), the initial abstraction index and the CN value in land use and land occupation found in the Cerrado watersheds using a rainfall simulator with different intervals of time and intensity. The rainfall simulator experiments were carried out in the Glória stream water catchment area, in the municipality of Uberlândia-MG. This watershed has several uses and occupation of land. From the data of the volume of precipitation and the volume of surface runoff, the water storage capacity of the rainfall simulator and the storage capacity of water with formulas were determined and, later, used to determine the CN values and the abstraction initial indices. The CN values contained in tables and graphs of the Natural Resources Conservation Service (NRCS) consider the Ia index as 20% of the maximum water storage capacity of the soil. However, there are variations in this index of Ia indicating that the value of 5% as the most adequate in several conditions. CN values and Ia indexes can be obtained by means of precipitation and runoff data obtained in river basins and by experiments with artificial rains, providing local information. The results of the rainfall simulator showed variations in the indices of Ia considering the different uses and occupation of the land, with indexes of 0.02 at indices higher than 0.5. The higher rainfall volume was the rainfall Ia (λsi) indexes and the Ia indices of the formula consider Ia as 20% of the soil water storage capacity (λp-q). In the use of the Coffee and Cerrado land, there were considerable variations in the runoff between the gutters, since it interferes with the soil water storage capacity and the CN values, a fact attributed to the trunk flow (Cerrado). The precipitation volume interferes with the CN values and the initial abstraction indexes. The soil hydrological group (HSG) were 'D' - brachiaria, corn, soybean and road, and 'C' in coffee and cerrado. The CN values obtained from the soil water storage capacity of the rainfall simulator (CNsi) were closer to the CN values tabulated in the antecedent conditions of humidity II or III (three antecedent humidity conditions I, II and III were used, and the higher the antecedent condition, the higher the CN values), and the CN values obtained with the water storage capacity of the soil that considers Ia = 0.2 · S (CNp-q) were close to the CN values tabulated in the condition antecedent of humidity I.